Using a finite element model of the thumb to study Trapeziometacarpal joint contact during lateral pinch. (January 2023) - Dong, Meilin; Kerkhof, Faes; Deleu, GertJan; Vereecke, Evie; Ladd, Amy
Abstract: Background: Finite element (FE) analysis is widely used in different fields of orthopaedic surgery, however, its application to the trapeziometacarpal joint has been limited due to the small size, complex biconcave-convex joint geometry, and complex musculature. The goal of this study was to improve upon existing models by creating a muscle-driven FE thumb model and use the model to simulate the biomechanical effect of hand therapy exercises and ligament reconstructive surgeries. Methods: Bone and cartilage geometry were based on a CT dataset of a subject performing a static lateral pinch task. A previously validated musculoskeletal model was utilized to extract electromyography (EMG)-driven muscle forces. Five ligaments with biomechanical significance were modeled as springs using literature values and attached according to their anatomical landmarks. Findings: The biomechanical consequence of various interventions was proxied as a change in the maximum cartilage stress. The result shows tightening the dorsal ligament complex (dorsal radial ligament, dorsal central ligament, posterior oblique ligament) is the most effective, achieving a stress reduction of 4.8%. Five exercises used in hand therapies were modeled, among which thenar eminence strengthening showed the most prominent stress reduction of 4.0%. Four ligament reconstructive surgeries were modeled, with Eaton-Littler reconstruction showed the most significant stress reduction of 25.0%. Interpretation: Among the routinely utilized treatment options for early thumb osteoarthritis, we found that three methods: dorsal ligament imbrication, thenar eminence exercise, and the Eaton-Littler method may confer biomechanical advantages cartilage loading. These advantages align with the clinically observed favorable outcomes. Highlights: We successfully built a muscle-driven finite element model of the trapeziometacarpal joint. Finite element analysis is useful for assessing clinical interventions for thumb osteoarthritis. The extent of simulated cartilage stress reduction correlates with clinical outcome.